Tail dependence between gold and sectorial stocks in China: Perspectives for portfolio diversication - Joscha Beckmann; Theo Berger; Robert Czudaj; Thi-Hong-Van Hoang (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2017)
This article analyzes the relationship between gold quoted on the Shanghai Gold Exchange and Chinese sectorial stocks from 2009 to 2015. Using different copulas, our results show that there is weak but significant tail dependence between gold and Chinese sectorial stock returns. This means that the dependence between extreme movements of the two assets is not pronounced and confirms the role of gold as a safe haven asset. Based on analyzing the efficient frontier, CCCGARCH optimal weights, hedge ratios and hedging effectiveness, we further show that adding gold into Chinese stock portfolios can help to reduce their risk. Gold appears to be the most efficient diversifier for stocks of the materials sector and the less efficient for the utilities sector. As a robustness check, we also compare gold to oil and indicate that gold is more efficient than oil in the diversification of Chinese stock portfolios.
Keywords: G11; C58; 330; Shanghai Gold Exchange; Chinese sectorial stocks; oil; copulas; portfolio implications